Novel topoisomerase II/EGFR dual inhibitors: design, synthesis and docking studies of naphtho[2',3':4,5]thiazolo[3,2-a]pyrimidine hybrids as potential anticancer agents with apoptosis inducing activity - Mourad, Mai A. E.; Elmaaty, Ayman Abo; Zaki, Islam; Mourad, Ahmed A. E.; Hofni, Amal; Khodir, Ahmed E.; Aboubakr, Esam M.; Elkamhawy, Ahmed; Roh, Eun Joo; Al-Karmalawy, Ahmed A. (Taylor & Francis, 2023)
Topoisomerases II are ubiquitous enzymes with significant genotoxic effects in many critical DNA processes. Additionally, epidermal growth factor receptor (EGFR) plays pivotal role in tumour growth and angiogenesis. A novel series of naphtho[2',3':4,5]thiazolo[3,2-a]pyrimidine hybrids have been designed, synthesised and evaluated for their topo IIa/EGFR inhibitory and apoptotic inducer activities. Cytotoxicity of the synthesised hybrids was evaluated against MCF-7, A549 and HCT-116 cell lines. Of the synthesised hybrids, 6i, 6a and 6c experienced superior cytotoxic activity compared to doxorubicin and erlotinib against the tested cancer cells. The molecular mechanism of these hybrids revealed their ability to successfully inhibit topo IIa and EGFR activities in micromolar concentration and may serve as topo II catalytic inhibitor. Moreover, these hybrids significantly arrested cell cycle at G2/M phase together with increased p53, caspae-7, caspase-9 levels and Bax/Bcl-2 ratio. The synthesised hybrids showed efficient binding pattern in molecular docking study and have acceptable drug likeness characters.